The Characterization Of Conversion Low-Rank Coal From East Kalimantan Indonesia Through Physical - Chemical Activation To Be Adsorbent - Alwathan, Alwathan; Mohd-Setapar , Siti Hamidah; Irwan, Muh.; Thahir, Ramli; Firman, Firman (Journal of Advanced Research Design, 2025)
One of the largest coal reserves in Indonesia is in the Kalimantan region, specifically in East Kalimantan. Generally, there are three types of coal, namely anthracite, bituminous, and lignite. Lignite is a type of coal that is widespread and has low economic value as an energy source. Its relatively low calorific value makes this type of coal unsuitable for use as fuel. One way to increase the added value of low-rank coal is to convert the coal into active carbon which can act as an adsorbent medium. The adequate carbon value found in this type of coal makes it possible to convert it into an absorbent material. One of the important parameters of the absorbent material is the iodine number. The process of converting coal into an absorbent material is through an activation process which is carried out through a carbonization stage at a temperature of 600°C for 3 hours then followed by chemical-physical activation of the carbonization material which is soaked in a chemical mixture of phosphoric acid and sodium carbonate in 2.5 M for 8 hours. and physically activated at 800 °C for 1.5 hours. The results of increasing the carbon content were obtained when the low-rank coal was initially 38.68%w, then increased in the carbonization process to 68.62%w, and at the time of activation, the amount of carbon reached 73.79%w, indicating that the low-rank coal conversion process was fulfilled in terms of the quality of the results obtained.